Manejo de la artritis enteropatica - Cujilema Rea, Sonia Estefania (Machala : Universidad Técnica de Machala, 2024)
Enteropathic arthritis is an inflammatory rheumatological condition associated with inflammatory bowel diseases such as Crohn’s disease and ulcerative colitis. It affects a considerable group of patients, presenting a significant challenge due to its complex diagnosis and multifaceted management. The aim of this study is to describe the management of Enteropathic Arthritis. An exhaustive search of scientific literature was carried out, including case studies, clinical trials, systematic reviews and meta-analyses published between 2019 and 2024. Medical databases such as PubMed, Scopus and Cochrane Library were used to collect relevant information. Pharmacological treatments for AE include sulfasalazine, methotrexate, azathioprine, and TNF inhibitors such as adalimumab and infliximab, which have shown efficacy in reducing inflammation and improving joint symptoms. New biological therapies such as ustekinumab and tofacitinib have shown promising results in patients who do not respond to conventional treatments. Non-pharmacological therapies, such as patient education, exercise, physiotherapy, feeding, use of probiotics and prebiotics, also play an essential role in managing EA, improving quality of life and adherence to treatment. In conclusion, the management of enteropathic arthritis requires a comprehensive approach that combines personalized pharmacological treatments with non-pharmacological therapies. Early identification of the disease and interdisciplinary management are essential to prevent long-term complications and improve the quality of life of patients.
La artritis enteropática es una condición reumatológica inflamatoria asociada a enfermedades inflamatorias intestinales como la enfermedad de Crohn y la colitis ulcerosa. Afecta a un grupo considerable de pacientes, presentando un desafío significativo debido a su diagnóstico complejo y manejo multifacético. El objetivo de este estudio es describir el manejo de la Artritis Enteropática. Se realizó una búsqueda exhaustiva de literatura científica, incluyendo estudios de caso, ensayos clínicos, revisiones sistemáticas y metaanálisis publicados entre 2019 aal 2024. Se utilizaron bases de datos médicas como PubMed, Scopus y Cochrane Library para recopilar la información relevante. Los tratamientos farmacológicos para AE incluyen la sulfasalazina, el metotrexato, la azatioprina y los inhibidores del TNF como adalimumab e infliximab, que han mostrado eficacia en la reducción de la inflamación y mejora de los síntomas articulares. Nuevas terapias biológicas como ustekinumab y tofacitinib han demostrado resultados prometedores en pacientes que no responden a tratamientos convencionales. Las terapias no farmacológicas, como la educación del paciente, ejercicio, fisioterapia, alimentación, uso de probióticos y prebióticos, también juegan un papel esencial en el manejo de la AE, mejorando la calidad de vida y la adherencia al tratamiento. En conclusión, el manejo de la artritis enteropática requiere un enfoque integral que combine tratamientos farmacológicos personalizados con terapias no farmacológicas. La identificación temprana de la enfermedad y un manejo interdisciplinario son fundamentales para prevenir complicaciones a largo plazo y mejorar la calidad de vida de los pacientes.
Keywords: ARTRITIS ENTEROPATICA; ARTRITIS; ENFERMEDAD DE CROHN; TRATAMIENTO